1992
DOI: 10.1080/07924259.1992.9672256
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic development of dwarf surf dam,Mulinia lateralis, oocytes treated with polar body suppressing agents

Abstract: Parthenogenesis following oocyte activation has been observed in a number of marine invertebrates, but the fate of parthenogenesis in bivalve mollusc embryos is unclear. We used the dwarf surf clam, Mulinia lateralis, to examine parthenogenetic development of KC1-activated oocytes using the polar body suppressing agents caffeine and heat or cytochalasin B. Development was followed by epifluorescence microscopy and flowcytometric analysis using the DNA-specific fluorochrome DAPI. All agents suppressed polar bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In fact, we ob scrved, as in Scarpa et al (1993), that the first division was later (70 min) in the treated embryos than in the control (50 min), which may also be a consequence of spermatie inhibition. Scarpa et al (1992) suggested that the absence of sperm in gynogenetic induction cou Id prevent l'irst mitosis, c1eavage and subsequent clevelopmcnt because of the absence of a paternal centrosome and Diter and Dufy (1990) that the first mitotic division and cleavage would be delayed by this means but that development could resume later. How ever, Hei Ibrunn (1925) suggested for Cummingia (Mollusca) and Washitani-Nemoto et al (1994) for As/erina pec/imfera (Echinodermata) that the inhibi tion ofpolar body expulsion in unfertilized eggs couId compensate for this lack of centrosome due to the presence of meiotic centrosomes which would allow normal mitosis and first cleavage to take place.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we ob scrved, as in Scarpa et al (1993), that the first division was later (70 min) in the treated embryos than in the control (50 min), which may also be a consequence of spermatie inhibition. Scarpa et al (1992) suggested that the absence of sperm in gynogenetic induction cou Id prevent l'irst mitosis, c1eavage and subsequent clevelopmcnt because of the absence of a paternal centrosome and Diter and Dufy (1990) that the first mitotic division and cleavage would be delayed by this means but that development could resume later. How ever, Hei Ibrunn (1925) suggested for Cummingia (Mollusca) and Washitani-Nemoto et al (1994) for As/erina pec/imfera (Echinodermata) that the inhibi tion ofpolar body expulsion in unfertilized eggs couId compensate for this lack of centrosome due to the presence of meiotic centrosomes which would allow normal mitosis and first cleavage to take place.…”
Section: Discussionmentioning
confidence: 99%